Effects of agricultural water withdrawal in the fluvial habitat of benthic macroinvertebrates in Chile - Guevara-Mora, Meyer; Pedreros, Pablo; Urrutia, Roberto; Figueroa, Ricardo (HIDROBIOLÓGICA, 2017)
The climatic and geographic characteristics of Central Chile allow the concentration of high water demand from agricultural activities in low order rivers. Changes in the hydrologic regime of these rivers should affect the habitat availability of endemic benthic macroinvertebrates. However, the impact of water diversion in the Chilean rivers is poorly understood. Goals. We want to determine the effects of water abstraction in the habitat of benthic macroinvertebrates with biotic indices. Methods. We sampled nutrients, macroinvertebrates, and morphological characteristics of three rivers affected by agricultural water extractions in the Itata basin (Chile). We assess the habitat alteration and benthic macroinvertebrate assemblage through the measurement of depth, current velocity, Froude number, wetted width/depth ratio, dissolved oxygen, and biotic indices. Results. Traditional methods of constructing the weirs affect the water level in the sampling sites. Most of the habitat parameters shows variation between the control and impact sampling sections, but only Shannon and Simpson diversity indices were statistical different. Conclusions. The increase in taxonomical resolution of benthic macroinvertebrates in the Mediterranean zone of Chile could improve detection of environmental impacts of water extraction. We suggest the use of biological traits in order to determine specific relationships between water withdrawals and environmental changes in low order rivers of Chile affected by water extraction.